Effect on albumin and fibronectin adsorption of silver doping via ionic exchange of a silica-based bioactive glass. (1st May 2023) - Barberi, Jacopo; Mandrile, Luisa; Giovannozzi, Andrea M.; Miola, Marta; Napione, Lucia; Rossi, Andrea M.; Vitale, Alessandra; Yamaguchi, Seiji; Spriano, Silvia
Abstract: Protein adsorption is a crucial step in the life of biomaterials for bone application, such as bioactive glasses. The investigation of adsorption mechanisms is a difficult task per se, which is even more complex on bioactive glasses due to surface reactivity. Here, the effect of silver doping by ionic exchange on the interaction of a silica-based bioactive glass with albumin and fibronectin, serum proteins related to osseointegration, is reported. The presence of silver does not change relevant surface properties such as topography, surface energy, wettability, or surface ζ potential. Nevertheless, the interactions with proteins are much different. The presence of silver significantly increases the adsorption of albumin and fibronectin and leads to a higher loss of secondary structure compared to the undoped surface, as a consequence of the interactions and bonding between silver and thiols in the cysteine residues. Selectivity of silver-doped glass is discovered: Ag enhances more adsorption and denaturation of albumin since it has more cysteines than fibronectin. It is also here observed that due to the formation of a hydrated silica gel layer during adsorption, proteins are not only present on the surface of the bioactive glasses, but also embedded inside the surface reaction layer.